Geo-disaster Laharic Flow along Putih River, Central Jawa, Indonesia - Sugeng Sapto Surjono; Ahmad Yufianto (Journal of Applied Geology, 2015)
In 2011, laharic flow transporting volcanic materials had significantly occurred along Putih River, causing severe damage in Jumoyo area, Magelang, Central Java, Indonesia. The disaster happened frequently until April 2011. The approximately 150 million cubic meter of volcanic materials expelled from 2010 Merapi eruption has been assumed as main cause of recent laharic flow. Although pyroclastic deposit mostly flew to south and southeastern direction through Woro, Gendol, and Opak Rivers, laharic flow apparently flew to the west – westward directions through Putih and Pabelan Rivers. This study will explain the mechanism of such disaster along Putih River from sedimentological point of view. Transport mechanism of laharic flow along river is strongly controlled by the slope and type of fluids. In the upper stream area, debris flow commonly occurs as gravity flow in the steep slope. To the downstream area, where more river and surface water infiltrates the volcanic material transportation, laharic flow mechanism transforms to hyperconcentrated flow. In the gently slope area, laharic flow decreases in concentration but increase in amount because of the accumulation influx from several river flows. Hyperconcentrated flow in Putih River is mostly generated by accumulation of river flow in the tributary area. In such area, loose volcanic materials are eroded easily by surface water. Rill and gully erosion bring volcanic material into main channel of Putih River, followed by intensive vertical erosion along upper stream that will produce bigger accumulation of volcanic material within laharic flow in the downstream area. Several sabo dams along the Putih River were damaged during early period of laharic flow due to this transportation mechanism. At the downstream of in Gempol Village, Jumoyo Area, the main channel of Putih River is shifting northwestward significantly due to Gendol Hill. On the other hand, river body in this settlement area is narrower compared to the upper stream area just before turning point. Both condition cause laharic flow to spill out from the channel and form an unconfined sheet debris flow with a 500 m width and around 2-4 m thick sediments. Although energy of transport is reduced significantly, but this flow is still able to transport abundant volcanic material ranging from silt to boulder. Traditional market and hundreds of houses were buried and the main road from Yogyakarta to Magelang city has been disconnected for several times due to this disaster. Keywords: Putih River, Laharic flow, Jumoyo